The Problems of Legal Regulation of the Organization of Games and Betting in the Republic of Armenia - Avetisyan, Vahram (Bulletin of Yerevan University C: Jurisprudence, 2021)
The article is devoted to identifying the existing problems of legal regulation of relations related to the organization of gambling in the Republic of Armenia, the legal nature of the agreement on the organization of gambling, analysis of the rights and obligations of organizers and participants in gambling, the problem of judicial protection of the rights and obligations of organizers and participants of gambling, as well as discussion some issues related to the prevention of addiction to gambling.
Keywords: rights and obligations of the game organizer; rights and obligations of game participants; problems of judicial protection; responsible gambling; betting (gambling) sweepstakes and lottery agreements